The moderation of intellectual capital in the relationship enterprise risk management and CSR toward company value - Yusvita Nena Arinta; Noraini Dwi Pebrianingsih (JAS (Jurnal Akuntansi Syariah))
Purpose – This study aims to find empirical evidence of the influence of enterprise risk management (ERM) and corporate social responsibility (CSR) on company value and the moderating role of intellectual capital. Method – This study uses a quantitative panel data regression method with a causal associative approach. The population in this study was manufacturing companies registered with Indonesian Sharia Stock Index (ISSI) in 2021-2023, totaling 98 companies. The research sample was filtered using a purposive sampling technique with several predetermined criteria to obtain a sample of 58 companies. Panel data collection was obtained from financial reports published through the website www.idx.co.id. Data analysis used multiple regression and moderation regression analysis (MRA) testing with the EViews 12 statistical tool. Findings – The results show that enterprise risk management negatively affects company value, while corporate social responsibility positively affects company value. Intellectual capital strengthens the relationship between enterprise risk management and company value. Intellectual capital weakens the relationship between CSR and company value. Implications – This study can advance the relevance of current theories and become a reference for further research, especially on company value. This research can be a reference for manufacturing companies advancing ERM and CSR best practices to increase company value.